Exploring the Impact of Social Media Marketing on Brand Engagement and Sales among Canadian Shoppers - Nowrid Amin, Kazi (Digital Repository of Theses, 2025)
This study explores the impact of social media marketing (SMM) on brand engagement and sales among Canadian shoppers, focusing on popular platforms such as Instagram, Facebook, and TikTok. It examines how different content types and user interactions influence purchasing decisions and investigates the connections between brand engagement, user-generated word-of-mouth, and consumer buying behavior. Furthermore, this study identifies key demographic and regional trends across Canada to offer actionable insights for marketers aiming to optimize their strategies. A mixed-method approach was employed, incorporating a comprehensive literature review and an online survey administered to 105 Canadian residents aged 18–45 years. The findings indicate that social media marketing positively influences brand engagement, which significantly enhances purchase intention. Moreover, brand engagement mediates the relationship between social media exposure and consumer purchasing behavior. This study recommends that brands invest in fostering consumer engagement through diverse content formats, influencer partnerships, and consistent publishing schedules. Additionally, leveraging engagement metrics and private consumer data can help refine content strategies tailored to specific demographic segments and regional preferences of the audience. The research also revealed notably higher engagement and sales activity among older consumers and those who reside in Eastern Canada. These insights contribute to the growing body of literature on digital marketing and offer practical implications for businesses in the Canadian retail space. As the social media landscape continues to evolve, this study emphasizes the importance of data-driven, regionally sensitive, and demographically targeted marketing strategies to remain competitive and relevant.